1994
DOI: 10.1111/j.1432-1033.1994.1097b.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Site of Synthesis and Dynamics of Cell Surface Re‐Expression of Polysialic Acid of the Neural Cell Adhesion Molecule

Abstract: Homopolymers of a-2,8-ketosidically linked sialic acid (polysialic acid) represent a posttranslational modification which, in mammals, appears to be unique for the neural cell adhesion molecule and the a subunit of sodium channels in brain. Under steady-state conditions, polysialic acid is detectable in the plasma membrane of different cell types but not in the cytoplasm. We have studied the site of synthesis and the cell surface re-expression of polysialic acid in a clonal subline of small cell lung carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 31 publications
2
47
1
1
Order By: Relevance
“…Although a3b1 does not mediate strong adhesion to FN, a3b1-dependent cell migration on FN has been previously reported (Yauch et al, 1998). SCLC also expresses another adhesion molecule, N-CAM, which mediates homophilic cell-cell adhesion, and may be involved in SCLC metastasis (Scheidegger et al, 1994). In the present study, however, the exogenous CD9 and In contrast to NSCLC, SCLC easily spreads into submucosal tissues and metastasizes to regional lymph nodes.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Although a3b1 does not mediate strong adhesion to FN, a3b1-dependent cell migration on FN has been previously reported (Yauch et al, 1998). SCLC also expresses another adhesion molecule, N-CAM, which mediates homophilic cell-cell adhesion, and may be involved in SCLC metastasis (Scheidegger et al, 1994). In the present study, however, the exogenous CD9 and In contrast to NSCLC, SCLC easily spreads into submucosal tissues and metastasizes to regional lymph nodes.…”
Section: Discussioncontrasting
confidence: 45%
“…CD9 associates with b1 integrins but not with N-CAM SCLC reportedly expresses adhesion proteins, b1 integrins and N-CAM, and both of these molecules are likely to regulate motility and metastasis of SCLC (Scheidegger et al, 1994;Bredin et al, 1998). To explore the mechanisms involved in the reduction of OS3-R5-pZCD9 motility, coimmunoprecipitation experiments using MoAbs against these molecules were performed (Figure 4b,left panel).…”
Section: Ectopic Expression Of Cd9 Into Os3-r5 Reduces Cell Motility mentioning
confidence: 99%
“…inoculated mice but in none of the s.c. injected ones probably because the s.c. environment is not favorable. In keeping with this hypothesis, other cell lines expressing PSA-NCAM such as the SCLC line NCL-H69 does not lead to lung metastases if injected s.c. (Scheiddeger et al, 1994). Moreover our recent work (Daniel et al, 2000) indicates that the PSA expressing SMtTW4 cells did not metastasize if grafted under the rat neck skin but did if implanted under the kidney capsule.…”
Section: Discussionmentioning
confidence: 99%
“…PSA-NCAM is expressed by several human neurectodermal tumors, including medulloblastomas, subclasses of neuroblastomas, small cell lung carcinomas, and rhabdomyosarcomas (Figarella-Branger et al, 1990;Molenaar et al, 1991;Scheiddeger et al, 1994). These tumors are known for their aggressive behavior and their ability to form metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we propose to introduce modified carbohydrate antigens on the surface of cancer cells to which a strong immunogenic response can be induced. We chose ␣2-8 polysialic acid (polysialic acid) as our target antigen, because although not a universal cancer antigen, it is found on a number of important cancers (11)(12)(13), and there is strong evidence that it is associated with metastasis (12,14). In addition we have previously demonstrated that in its N-propionylated form (NPr polysialic acid) 1 it is an excellent immunogen (15,16).…”
mentioning
confidence: 99%